Effectiveness And Contribution Of Land And Building Tax Revenue In Sragen City - Abdul Mustofa Iqbal Asyrof; Dilivia Dama Ivonne; Galih Wicaksono; Deviana Safitri (Journal of Law, Administration, and Social Science, 2023)
The aim of this research is to determine the effectiveness of Land and Building Tax revenue, as well as to find out the socialization strategy as an effort to make Land and Building Tax (PBB) revenue more effective in Sragen Regency. The method used is quantitative, by collecting several data, literature studies, and also other supporting information. According to Law no. 28/2009 concerning Rural and Urban Land and Building Tax (PBB-P2) is one of the taxes managed by the Regional Government. The results of this research show that the growth in PBB-P2 revenue in Sragen Regency has reached the target set over the past 3 years. The level of effectiveness of PBB-P2 in Sragen Regency has been in the criteria of being very effective in the last 3 years, while the level of PBB-P2 contribution to Sragen Regency's Original Regional Revenue (PAD) is very low. The growth rate of PBB-P2 revenue after the enactment of Law no. 28/2009 experienced a decrease in percentage, this was because the target set by the regional government was greater than the target set by the central government.